Erratum: Design and sensitivity of the Radio Neutrino Observatory in Greenland (RNO-G) ... - Aguilar, J. A.; Allison, P.; Beatty, J. J.; Bernhoff, H.; Besson, D.; Bingefors, N.; Botner, O.; Buitink, S.; Carter, K.; Clark, B. A.; Connolly, A.; Dasgupta, P.; et al. (Deutsches Elektronen-Synchrotron, DESY, Hamburg, 2023)
Journal of Instrumentation 18(03), E03001 (2023). doi:10.1088/1748-0221/18/03/E03001 ... : This is a correction for 2021 JINST 16 P03025 ...